The relationship between the quality of the workforce and educational factors in Cibogo Village, Subang Regency - Tiana, Dian; Saviela, Hasvika; Santoso, Oktavian Dwi (Universitas Pendidikan Indonesia, 2024)
This program examines the potential and challenges of Cibogo Village, Subang Regency's workforce during the Community Services Program (Kuliah Kerja Nyata or KKN) activities conducted by the Universitas Pendidikan Indonesia. Despite Cibogo Village having a significant workforce, particularly within the productive age range, disparities in the quality of the workforce are the primary focus. Data indicates that most of the workforce has only basic education, such as completing primary school or its equivalent, creating obstacles in meeting the demands of an increasingly developing industrial era. Additionally, there is an imbalance in job participation between men and women, with a significant number of women choosing to be homemakers. A descriptive approach with data collection through observation was used in this program. The results suggest the need for efforts to improve education and skills training to enhance the quality of the workforce in Cibogo Village. Furthermore, a deeper understanding of gender roles in job participation is essential to create equality and empowerment between men and women. Based on this, Cibogo Village can obtain an overview of its potential, mainly related to factors that can be of concern for improvement, especially in terms of gender equality, absorption of science and technology, and development of UMKMs.